PENERAPAN INTERNATIONAL FINANCIAL REPORTING STANDARS TERHADAP HUBUNGANNYA DENGAN KOMPARABILITAS PENGUNGKAPAN ATAS AMANDEMEN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NO.16 - HELMI HERAWATI HERAWATI; Haryadi Haryadi (Universitas Prof.Hazairin,SH Bengkulu, 2018)
Implementation of International Financial Reporting Standards Against Their Relationship With Comparability Disclosure of Amendments to Statement of Financial Accounting Standards No.16 (Empirical Study of Manufacturing Companies Listed on Indonesian Stock Exchange of Go Public).This study aims to determine the application of IFRS to its relationship with the comparability of disclosure of amendment of PSAK No. 16 on the financial statements of Manufacturing Companies that have Go Public and listed on the Indonesia Stock Exchange. The population in this study are all manufacturing companies that have Go Public and listed on the Indonesia Stock Exchange in 2012 -2016. While the sample of this study is determined by purposive sampling method to obtain 405 samples during the year of research. Data obtained from the index of disclosure of PSAK 16, financial statements of manufacturing companies in Indonesia Stock Exchange year 2012 - 2016. The method of analysis using descriptive statistics with multiple regression analysis analysis, with a significant level set 5% (? = 0.005). The analysis tool used is SPSS 16 program.From the calculation results obtained by the linear regression equation is DISCL = 0.975 - 1.511 (IDH) - 0.008 (IFRS1) + 1.494E-5 (IFRS2) + 0.267 (IDH * IFRS1) + 2.198 (IDH * IFRS2) + 0,000 (SIZE) - 0 , 17 (ROA) - 0.29 (SCALEDB) - 1.025E-8 (LEV) + e. based on the result of F test it is known that Fcount> Ftable (395> 1.65251), it can be concluded that there is significant influence of variable IDH (x1), IFRS1 (x2), IFRS2 (x3), IDH * IFRS1 (x4), IDH * IFRS2 (x5), SIZE (x6), ROA (x7), SCALEDB (x8) and LEVERAGE (x9) simultaneously or simultaneously to the Disclosure Level of PSAK 16 (DISCL). Means the F value of 1522.755 with a probability value of 0.000 lower than 0.05. This means that the regression model in this study can be used. And result of t test show that influence of independent variable, interaction and control have significant negative effect to dependent variable.Based on the result of determination coefficient test, it is known that the adjusted value of is 0,971. It is stated that 97,1% of variation of disclosure index of PSAK 16 can be explained significantly by independent variable used in this research that is IDH, IDH * IFRS1, IDH * IFRS2 and control variable SIZE, ROA, SCALEDB, LEVERAGE. While the rest of 2.9% the disclosure index of PSAK 16 can be explained by other variables outside the model. It can be concluded that the application of the latest IFRS convergence has a positive effect on PSAK 16